Bureaucrats and Public Procurement - Dieter Bös (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper deals with a Niskanen type of public-procurement agency. It is shown that the procurement game should be separated into an investment game and a project game, the first game to be played before nature determines the actual real-izations of benefit and costs of the project, the second game to be played afterward. In the first game the relationship-specific investments of agency and seller are determined, in the second game the decision on the production of the project is taken. In contrast to many other incomplete-contract papers, in our Niskanen setting it is meaningless to write one and only one contract which refers to both investment and production. Welfare-optimal procurement of the project can be attained under relatively weak assumptions; welfare-optimal investments of the seller (and only of the seller) may result under special circumstances; welfare-optimal investments of both agency and seller cannot be reached.
Keywords: 330; Bureaucracy; Procurement; incomplete contracts